Use of Phloem Exudate Technique in the Study of Amino Acid Transport in Pea Plants - Urquhart, Aileen A. (1981)
The phloem exudation technique using ethylenediaminetetraacetic acid (EDTA) was evaluated in studies of amino acid translocation in Pisum sativum L. seedlings. Exudation of phloem sap from cut petioles of fully expanded leaves was enhanced by EDTA (20 millimolar disodium salt [pH 7.0]). Amino acids (mainly asparagine, homoserine, glutamate, and also aspartate and serine) were present in petiole exudates from EDTA-treated leaves at levels which were commonly 5- to 10-fold (or more) higher compared with water-treated controls. Exudation was greater from darkened leaves, and the pattern of amino acids was markedly different from the more uniform mixture leaking from water-treated controls. After feeding (14)C-labeled amino acids to the leaf blade, distribution of radioactivity in components of the exudate differed from that of the leaf tissue, suggesting selectivity of amino acid loading. [(14)C]Asparagine was converted to 2-hydroxysuccinamic acid and to other amino acids by the leaf, but was recovered in exudate mainly as asparagine (60%) and aspartate (30%). Similarly, in the exudate, 65 to 70% of the label from [(14)C]-aspartate was in amino acids, although in the leaf tissue 50% was in the organic acid fraction and only 11% remained as aspartate. Metabolism of asparagine and aspartate was essentially the same in intact leaf blades as in EDTA-treated leaves. Despite the possibility of EDTA damage in the petiole, phloem loading of amino acids appeared to be relatively unimpaired. Although the amount of labeled material appearing in the exudate is less than the amount translocated in the intact plant, the technique is useful in the study of amino acid transport.